ENTRY AND CIRCULATING FLOW RELATIONSHIP AT A ROUNDABOUT (Malaysian Journal of Civil Engineering, 2018)
This study examined the two formulas stated in the Arahan Teknik (J) 11/87 of theMalaysian Public Work Department to estimate the capacity of small and conventionalroundabouts. Field survey, which cover the roundabout inventories, and vehicle classification werecarried out. Vehicle classification survey indicates lower entry flows at the single lane entriescompared to the multilane entries for both morning and evening peak hours. Statistical analysiswas used to identify the correlation between the circulating flows, entry flows and the entry width.Results showed that the capacity obtained from the weaving concept was generally higher than theregression equations for the single and multi entries. The difference between these results may bedue to the regression equations that consider the interaction between the entry and circulating flowand the geometric parameters, while the Arahan Teknik (J) 11/87 only address the geometricparameter. The entry flows for both single and multilane entries were highly dependent on thecirculating flows.